Industrial Robotics New Paradigms - Grau, Antoni; Wang, Zhuping (IntechOpen, 2020)
In this book, a new approach to the Industry 4.0 revolution is given. New policies and challenges appear and education in robotics also needs to be adapted to this new era. Together with new factory conceptualization, novel applications introduce new paradigms and new solutions to old problems. The factory opens its walls and outdoor applications are solved with new robot morphologies and new sensors that were unthinkable before Industry 4.0 era. This book presents nine chapters that propose a new outlook for an unstoppable revolution in industrial robotics, from drones to software robots